Islands of the damned : a Marine at war in the Pacific - Burgin, R. V.; Marvel, Bill. (New York : NAL Caliber, 2010)
Burgin reveals his experiences as a Marine at war in the Pacific Theater. Company K confronted snipers, ambushes along narrow jungle trails, and howling banzai attacks as they island-hopped from one bloody battle to the next.
Burgin reveals his experiences as a Marine at war in the Pacific Theater. Company K confronted snipers, ambushes along narrow jungle trails, and howling banzai attacks as they island-hopped from one bloody battle to the next.
Includes bibliographical references and index.
Keywords: Burgin, R. V; United States. -- Marine Corps. -- Marines, 5th. -- Battalion, 3rd.; United States. -- Marine Corps -- Biography; World War, 1939-1945 -- Campaigns -- Pacific Area; World War, 1939-1945 -- Personal narratives, American; Marines -- United States -- Biography